BIOSORPTION OF MN (II) IONS FROM AQUEOUS SOLUTION BY JERUSALEM ARTICHOKE (HELIANTHUS TUBEROSUS L.) STALKS - Tsvetko PROKOPOV (Stefan cel Mare University of Suceava, 2017)
The purpose of this paper is to tested Jerusalem artichoke stalks as a cheap biosorbent for its ability to remove Mn (II) ions from aqueous solution. Batch experiments were carried out to evaluate the effects of pH, biosorbent particle size, dosage, initial metal concentration and contact time. The maximum removal efficiency of about 97.0 % was reached at pH 8.0 by using of biosorbent particle size 530-850  m, adsorbent dosage 30 g/L, initial metal concentration 10 mg/L, temperature 20 oC, agitation speed 120 rpm and contact time 90 min. Pseudo-first order and pseudo-second order models were applied to describe the obtained kinetic data. The pseudo-second order model provided the best fit for experimental data with coefficient of determination R2 > 0.99. Freundlich and Langmuir isotherm models were used to describe metal adsorption. Equilibrium data agreed well with Langmuir isotherm with R2 = 0.993.